Fostering Financial Discipline in MSMEs through Practical Financial Reporting Assistance: A Community Service Program at Warung Sarapan Mba Yati - Dina Hastalona; Anto Tulim; Sugito Sugito; Aryani Sairun; Dedi Suryanta Surbakti; Taufik Azmi Harahap (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in economic growth; however, many MSMEs still face challenges in financial management, particularly in maintaining systematic financial records and preparing simple financial reports. Low levels of financial literacy often result in poor financial decision-making and the mixing of personal and business finances. This community service program aimed to foster a culture of financial discipline through mentoring in the preparation of practical financial reports for Warung Sarapan Mba Yati. Unlike previous programs that primarily focused on short-term bookkeeping training, this activity integrated practical financial reporting templates with intensive mentoring tailored to the MSME’s daily business transactions. The program was conducted over three weeks and involved three participants consisting of the business owner and family members involved. The implementation stages included observation, socialization, training, hands-on practice, mentoring, and evaluation. Program effectiveness was assessed using pre-test and post-test evaluations, direct observation, and assessment of participants’ financial recording outputs. The results showed a significant improvement in participants’ financial management competencies, with the average score increasing from 32.5% before the program to 89.5% after mentoring. Participants were able to independently prepare daily cash records, classify income and expenses, and produce a simple income statement showing a monthly net profit of IDR 4,250,000. Furthermore, participants began consistently separating personal and business finances and implementing routine transaction recording practices. These findings indicate that the mentoring program effectively improved bookkeeping skills and promoted a sustainable culture of financial discipline, thereby supporting better business management and long-term MSME sustainability.